On the Survival of Rare Plants – Hungarian Museums in the Decade of Changeover - Hanneleena Hieta (Savolainen) (Journal of Ethnology and Folkloristics)
The purpose of this article is to assess changes in the museum institution as a response to the social environment. A metaphor of natural evolution is employed. The idea of ‘effective history’ is also introduced. The case in point in this article is Hungary and its museums. The period after 1962 witnessed strong growth in the public sector. The growth was seriously hampered by inflation in the second half of the 1980s. The environment, however, did not change drastically until the 1990s when there were dramatic changes in the amount and principles of public funding. A case study is introduced to mirror these changes.